3551 Intermittent Theta Burst Stimulation to Relieve Depression and Executive Function impairment in older adults. (27th March 2019) - Cristancho, Pilar; Berger, Jacinda; Kamel, Lojine; Araque, Manuela; Deanna, Barch; Eric, Lenze
Abstract : OBJECTIVES/SPECIFIC AIMS: The objective of the study is to examine the ability of iTBS to improve depression and executive impairment in depressed older adults. If effective, this treatment will have the potential to improve the quality of life in LLD. METHODS/STUDY POPULATION: From 12- 2016 to date older adults (60 – 85 y/o) in a major depressive episode, with evidence of executive dysfunction (on the NIH Tool Box battery) were enrolled. iTBS protocol: This brief paradigm (3 min 9 seconds duration) was administered on weekdays for four weeks (20 sessions total). Stimulation intensity was set up to 120% of the observed motor threshold. Depression primary outcome: Change in the Montgomery Asberg Depression Rating Scale (MADRS) from baseline to the end of iTBS course. Executive function primary outcome: Change in executive measures from the electronic NIH Tool Box cognitive domain battery8. Executive secondary outcome: Change in scores from baseline to the end of iTBS on the Frontal Systems Behavior Scale (FrSBe), this self reported instrument measures dys-executive behavior. Statistical Analysis: paired t-test examined changes in depression and executive variables from baseline to post iTBS. Pearson correlation examined the association between degree of mood improvement and degree of improvement in executive function. SPSS v 24 was used for all analyses. RESULTS/ANTICIPATED RESULTS: We examined 11 subjects. Primary outcomes: Patients showed a significant decrease in scores on the Montgomery Asberg Depression Rating Scale (MADRS) from baseline Mean (M) = 27.73, Standard Deviation (SD) 8.2 to the end of 4 weeks of iTBS: M = 15.91, SD = 10.05, t = 7.4, p < .001. The Flanker Inhibitory Control and attention test significantly improved from baseline M = 91.0, SD = 7 to the end of iTBS M = 98.7, SD = 12.8, t = −2.9, p = .014 (higher scores at week 4 denote improvement). The List Sorting Working Memory test and the Dimensional Change Card sort a measure of cognitive flexibility improved but did not reach statistical significance. The self reported executive measure improved from baseline M = 48.6, SD = 9.4 to post iTBS M = 39.4, SD = 8.5, t = 3.8, p = .003 (lower scores at week 4 denote improvement). We also examined whether the degree of improvement in depression related to the degree of improvement in executive function. We found positive correlations between change in mood scores with iTBS with change in executive scores with iTBS, with a strong relationship with working memory r = 0.34. Tolerability and Side effects: Common side effects were twitching in facial muscles during the stimulation (n =11), headaches (n =10) and pain or discomfort at the stimulation site and face (n =4). One participant withdrew due to intolerance to the stimulation. DISCUSSION/SIGNIFICANCE OF IMPACT: The iTBS paradigm was effective in improving mood and executive function in older adults. Both the psychometric measure and the self reported executive function measure (indicative of dysexecutive behavior) reflected improvements post iTBS. Improvement in executive function was correlated with depression improvement. We targeted the Dorso Lateral Prefrontal cortex, which exhibits decreased connectivity with the dorsal anterior cingulate in depressed elderly and is a key in orchestration of executive function. Our findings are consistent with the conceptualization of depression as a circuit level disorder affecting interconnected networks involving mood and cognition. Although we demonstrated potential therapeutic effects, the mechanism of action of iTBS remains unknown. We are presently conducting a randomized controlled trial to examine the effects of iTBS on brain connectivity using functional MRI. Results of this study underway will hopefully demonstrate engagement of the TMS target and contribute to a neurocircuitry based approach treatment of geriatric depression.